2014
DOI: 10.14814/phy2.12239
|View full text |Cite
|
Sign up to set email alerts
|

Chronically endurance-trained individuals preserve skeletal muscle mitochondrial gene expression with age but differences within age groups remain

Abstract: Maintenance of musculoskeletal function in older adults is critically important for preserving cardiorespiratory function and health span. Aerobic endurance training (ET) improves skeletal muscle metabolic function including age‐related declines in muscle mitochondrial function. To further understand the underlying mechanism of enhanced muscle function with ET, we profiled the gene transcription (mRNA levels) patterns by gene array and determined the canonical pathways associated with skeletal muscle aging in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Several lines of evidence have linked PGC-1α with muscle maintenance. First, PGC-1α and its downstream targets are reduced in skeletal muscle from older individuals when compared to young adults (Conley et al 2000;Short et al 2005;Safdar et al 2010;Joseph et al 2012). Second, PGC-1α content is positively correlated with oxidative capacity and training status in healthy young individuals (Garnier et al 2005) and similar correlations have been made with gait speed in older adults (Joseph et al 2012).…”
Section: Molecular Mechanisms Mediating Exercise-induced Mitochondriamentioning
confidence: 72%
See 1 more Smart Citation
“…Several lines of evidence have linked PGC-1α with muscle maintenance. First, PGC-1α and its downstream targets are reduced in skeletal muscle from older individuals when compared to young adults (Conley et al 2000;Short et al 2005;Safdar et al 2010;Joseph et al 2012). Second, PGC-1α content is positively correlated with oxidative capacity and training status in healthy young individuals (Garnier et al 2005) and similar correlations have been made with gait speed in older adults (Joseph et al 2012).…”
Section: Molecular Mechanisms Mediating Exercise-induced Mitochondriamentioning
confidence: 72%
“…First, PGC-1α and its downstream targets are reduced in skeletal muscle from older individuals when compared to young adults (Conley et al 2000;Short et al 2005;Safdar et al 2010;Joseph et al 2012). Second, PGC-1α content is positively correlated with oxidative capacity and training status in healthy young individuals (Garnier et al 2005) and similar correlations have been made with gait speed in older adults (Joseph et al 2012). Lastly, mouse overexpression studies demonstrate that mildly increasing PGC-1α levels in skeletal muscle prevents age-related muscle atrophy by augmenting processes related to mitochondrial turnover and quality control (Wenz et al 2009).…”
Section: Molecular Mechanisms Mediating Exercise-induced Mitochondriamentioning
confidence: 99%
“…Changes in gene expression are variable in trained individuals, and metabolic remodeling is not uniform in training humans (Johnson et al, 2014). Moreover, exercise is inherently hormetic.…”
mentioning
confidence: 99%
“…However, while a large body of research supports the importance of mitochondrial senescence in sarcopenia, contradictory theories emphasize on the detrimental effects of inactivity for muscle homeostasis, attributing changes in muscle energy capacity to a sedentary lifestyle of the elderly (10). Recently, Johnson et al compared the effects of endurance training on muscular mitochondrial health in the elderly (11). Interpreting changes of mitochondrial function on a transcriptional level, they concluded that in sarcopenia there is a decrease of mitochondrial genes and pathways involved in oxidative phosphorylation, which was compensated by endurance training in the older cohort compared to the sedentary cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Interpreting changes of mitochondrial function on a transcriptional level, they concluded that in sarcopenia there is a decrease of mitochondrial genes and pathways involved in oxidative phosphorylation, which was compensated by endurance training in the older cohort compared to the sedentary cohort. Interestingly, however, physical activity had a more profound effect on the transcriptional profile in the younger cohort than in the elderly (11). …”
Section: Introductionmentioning
confidence: 99%